Inter-strain differences of serotonergic inhibitory pain control in inbred mice - Myrczek Thekla; Häussler Annett; Albuquerque Boris; Wijnvoord Nina; Popp Laura; Tegeder Irmgard (SAGE Publishing, 2010)
Abstract Background Descending inhibitory pain control contributes to the endogenous defense against chronic pain and involves noradrenergic and serotonergic systems. The clinical efficacy of antidepressants suggests that serotonin may be particularly relevant for neuropathic pain conditions. Serotonergic signaling is regulated by synthesis, metabolisms, reuptake and receptors. Results To address the complexity, we used inbred mouse strains, C57BL/6J, 129 Sv, DBA/2J and Balb/c, which differ in brain serotonin levels. Serotonin analysis after nerve injury revealed inter-strain differences in the adaptation of descending serotonergic fibers. Upregulation of spinal cord and midbrain serotonin was apparent only in 129 Sv mice and was associated with attenuated nerve injury evoked hyperalgesia and allodynia in this strain. The increase of dorsal horn serotonin was blocked by hemisectioning of descending fibers but not by rhizotomy of primary afferents indicating a midbrain source. Para-chlorophenylalanine-mediated serotonin depletion in spinal cord and midbrain intensified pain hypersensitivity in the nerve injury model. In contrast, chronic inflammation of the hindpaw did not evoke equivalent changes in serotonin levels in the spinal cord and midbrain and nociceptive thresholds dropped in a parallel manner in all strains. Conclusion The results suggest that chronic nerve injury evoked hypernociception may be contributed by genetic differences of descending serotonergic inhibitory control.